PENGARUH MODEL INDEX CARD MATCH TERHADAP HASIL BELAJAR SISWA KELAS V SD NEGERI 21 PALEMBANG - Sherli Sherli Ramadanti (Universitas Negeri Medan, 2023)
Abstract :The Effect Of The Index Card Match Model On The Students Learning Outcomes In Class V Sd Negeri 21 Palembang. This study aims to determine the effect of the index card match modl on the learning outcomes of fifth grade students at SD Negeri 21 Palembang. The research method in this study was using an experimental method with the design of The Nonequivalent Control Group Design, the population in this study amounted to 90 students from all fifth grade students of SD Negeri 21 Palembang. The data collection technique in this study used multiple choice test questions. Contect validaty was calculated from experience judgment and construct validity was calculated using product moment correlation by Pearson and reliability using Cronbach's Alpha. The data analysis technique used in this study is the normality test with the kolmogorof-smirnov test, the homogeneity test with the F test and hypothesis testing with the Independent Sample T test. The results showed that there was an effect of the index card match model on the learning outcomes of fifth grade students at SD Negeri 21 Palembang. It is shown from the results of the Independet Sample T test of Pretest and Posttest data on learning outcomes, the value of ????????????????????????= 3,98 > ????????????????????????= 1,672, then Ho is rejected amd Ha is accepted.